Assuring learning and teaching standards through inter-institutional peer review and moderation : final report of the project. - Krause, Kerri-Lee; Scott, Geoff; Aubin, Kate; Alexander, Heather; Angelo, Tom; Campbell, Stuart; Carroll, Martin; Deane, Elizabeth; Nulty, Duncan; Pattison, Pip; Probert, Belinda; Sachs, Judyth; et al. (Australia. Office for Learning and Teaching, 2014)
Australian higher education requires a relevant and feasible way to assure the validity, reliability and comparability of assessment outcomes and achievement standards in equivalent university programs, subjects/units of study across the nation. This project addresses the Tertiary Education Quality and Standards Agency (TEQSA) imperative to demonstrate sector-level, self-regulated, robust approaches for assuring quality and standards and highlights the role of peer review. The project tested an inter-institutional blind peer review methodology using a broad, representative range of university partners. In the approach, groups of academics teaching equivalent units of study in two partner universities undertook a blind review of both the assessment inputs (subject outlines, assessment tasks and marking criteria) and assessment outcomes (de-identified samples of assessment at different grade levels) from a partner university teaching a similar final year subject. The project has successfully achieved its aim of developing a validated, robust approach for assuring subject achievement standards through inter-university moderation in common final year subjects across disciplines. The project not only developed a viable approach to interinstitutional moderation of assessment inputs and outcomes but also found high levels of broad agreement amongst peer reviewers on assessment standards and grading in 12 discipline areas, thus establishing that the process used is a powerful professional development tool in its own right. Key implementation strategies have also been identified to enable institutions interested in using the approach to adopt or adapt it sustainably and effectively. The project has delivered: a user guide; a peer review template; a sample policy for interinstitutional peer review; guidelines on how best to respond to areas for improvement identified through the peer reviewer process; strategies for publishing selected inter-institutional peer review outcomes; and recommendations on how to improve national and institutional policy and practice. The project website and all information and resources related to the project is available at: www.uws.edu.au/latstandards. [Author abstract]